Morphological and Functional Study of Regenerated Chorda Tympani Nerves in Humans - Shibamori, Yoshiyuki; Yamamoto, Takehito; Saito, Takehisa; Manabe, Yasuhiro; Ohtsubo, Toshio; Yamagishi, Takahiro; Saito, Hitoshi (Annals of otology, rhinology & laryngology, 2000)
It is still unclear whether the chorda tympani nerves in humans regenerate after being severed during middle ear surgery, although functional studies have demonstrated recovery of taste 1 to 2 years after surgery. To date, 12 cases of regenerated chorda tympani nerves have been found in our series of patients during secondary surgery. The regenerated nerves of 3 cases of the 12 were removed as samples during secondary surgery to detect regenerated myelinated axons. All regenerated nerves were in the submucosal connective tissue layer of the reconstructed eardrum. In the regenerated nerves, myelinated nerve fibers existed in a small fascicle or in connective tissue, but the number of myelinated axons was low compared with that in normal subjects (1,752 ± 78; n = 3), and the distribution was sparse. The total number of regenerated myelinated axons varied from 141 (8.3%) to 979 (55.9%). From a functional study using electrogustometry, incomplete recovery of electrogustation was observed in all 3 cases before secondary surgery, suggesting that chorda tympani nerves actually regenerate in the middle ear and do function.